Analysis of Internal Control to Account Receivable Service at PT. Bosowa Berlian Motor Manado - Sarah Anastasya Putri Nusa; Robert Lambey Lambey; Peter Kapojos (PT FORMOSA CENDEKIA GLOBAL, 2023)
Internal control is an activity that occurs within the company, namely by paying attention to the performance of each part of the company to determine if it is in accordance with applicable standards or regulations to achieve company goals. The purpose of this study is to find out about the course of internal control on Receivables that occurs at PT. Bosowa Berlian Motor Manado. The type of research used is descriptive-qualitative, with data collection techniques namely observation, interviews, and documentation. Based on the research results, using components from COSO that relate to internal control on accounts receivable at PT. Bosowa Berlian Motor Manado is still less effective in internal control, especially in service receivables. Judging from the Components of the Control Environment, Risk Assessment, Control Activities, Information and communication, and Monitoring Activities, some of these components have not been implemented properly, so that many service receivables have not been paid and some are even uncollectible.